2000
DOI: 10.1080/02841860050215963
|View full text |Cite
|
Sign up to set email alerts
|

Serum Thyroglobulin as a Risk Factor for Thyroid Carcinoma

Abstract: Samples from a biological serum bank taken up to 23 years prior to diagnosis of thyroid carcinoma were analysed for human thyroglobulin, thyroid-stimulating hormone and thyroxin. After exclusions, the final study material consisted of 59 cases of papillary and follicular carcinomas. These cases were compared with 164 controls, matched for sex, age and time of sample taking. The most interesting finding was that concentrations of thyroglobulin in serum were abnormally elevated in cases compared with controls, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Another interesting finding in our cohort was that the risk of thyroid cancer was approximately four times higher in those with serum levels of TG > 60 ng/mL compared with those with TG < 15 ng/mL. This association persisted after adjustment for presence of diffuse goiter or ultrasound-detected nodules at the first screening examination and is consistent with a previous report suggesting that serum TG, in addition to its established link with iodine deficiency, may be an early marker of thyroid cancer risk (Hrafnkelsson et al 2000). …”
Section: Discussionsupporting
confidence: 90%
“…Another interesting finding in our cohort was that the risk of thyroid cancer was approximately four times higher in those with serum levels of TG > 60 ng/mL compared with those with TG < 15 ng/mL. This association persisted after adjustment for presence of diffuse goiter or ultrasound-detected nodules at the first screening examination and is consistent with a previous report suggesting that serum TG, in addition to its established link with iodine deficiency, may be an early marker of thyroid cancer risk (Hrafnkelsson et al 2000). …”
Section: Discussionsupporting
confidence: 90%
“…Pellegriti et al reported that circulating TSH receptor-stimulating antibodies (TSHR-Abs) were present in all patients with Graves’ disease [ 18 ], implying an association between TSHR-Abs and elevated levels of thyroid hormones. TSHR-Abs are known to stimulate the same intracellular signal pathways as TSH, which has mitogenic and antiapoptotic effects on thyroid follicular cells and thus may play a role in thyroid cancer initiation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the TSH data in these studies were obtained from patients presenting with thyroid nodules. Only one study included a healthy control group and reported that no differences were found between thyroid cancer and healthy control groups in TSH values [27]. Kim et al [26] compared TSH levels obtained from euthyroid patients with differentiated thyroid cancer to TSH levels from controls in the general population.…”
Section: Discussionmentioning
confidence: 99%